KELAYAKAN FINANSIAL AGROINDUSTRI PEKTIN DAN PAKAN TERNAK TERFERMENTASI BERBAHAN BAKU KULIT PISANG - Shanti Akhiriani; Soetriono Soetriono; Nurhayati Nurhayati (Faculty of Agricultural Technology, University of Jember, 2014)
Banana peel has the potential to be processed into pectin and fermented feed products. This study aims to determine the financial feasibility of the agro-industry of banana peel pectin and fermented feed, and sensitivity to the increasing of the raw material prices, rising prices and declining selling prices. The study used a descriptive and analytical approach. The results showed that pectin agro-industry and fermented feed from banana peel as raw material feasible to be developed based on five criteria: Net Present Value (NPV), Gross B / C, Net B / C, Internal Rate of Return (IRR) and Payback Period (PP). Banana peel pectin agroindustry was feasible to manage based on five financial feasibility criteria, including: (1) Net Present Value (NPV) of IDR 720,114,699.00 (> 0); (2) Gross B/C of 1.06 (> 1); (3) Net B/C of 2.34 (> 1); (4) Internal Rate of Return (IRR) of 40.89% (> 13%); and (5) Payback Period (PP) of 2.9 (<10 years). Fermented animal feed agroindustry was feasible to manage based on five financial feasibility criteria, that is: (1) NPV of IDR 366,118,110.00 (> 0); (2) Gross B/C of 1.16 (> 1); (3) Net B/C of 1.93 (> 1); (4) IRR of 32.54% (> 13%); and (5) PP of 3.7 (<10 years).Keywords: financial feasibility, banana peel, pectin, fermented feed, sensitivity